DETERMINANTS OF INDONESIAN PRIMARY TEACHERS’ ADOPTION OF ARTIFICIAL INTELLIGENCE IN SCIENCE TEACHING - Zulherman Zulherman; Abu Bakar Ahmad Mansor (Program Studi PGSD Universitas Flores, 2026)
The integration of artificial intelligence (AI) in education has gained increasing attention; however, its adoption in elementary science teaching remains uneven. This study aims to evaluate the factors influencing Indonesian elementary school teachers’ adoption of AI in science teaching by extending the Technology Acceptance Model (TAM). An exploratory quantitative research design was employed involving 322 elementary school science teachers in Indonesia. Data were collected using a structured questionnaire that measured six latent constructs: Perceived Usefulness, Perceived Ease of Use, Attitude Toward Use, Behavioral Intention, Self-Efficacy, and AI Anxiety. The data were analyzed using structural equation modeling. The findings revealed that perceived usefulness was the strongest predictor of teachers’ behavioral intention to adopt AI in science teaching. In addition, self-efficacy and AI anxiety significantly influenced teachers’ perceptions and attitudes toward AI integration. These results indicate that AI adoption in elementary science education is shaped not only by technological perceptions but also by psychological and pedagogical factors, including teachers’ confidence and learning experiences. This study extends the TAM framework by integrating psychological antecedents in a developing country context and provides theoretical and practical insights for developing teacher-centered strategies to support effective AI integration in elementary science teaching.